Factorisation using common factors

Factorization by common factors

Ex 12.1, 1 (i)

Ex 12.1, 1 (ii)

Ex 12.1, 1 (iii) Important

Ex 12.1, 1 (iv) Important

Ex 12.1, 1 (v)

Ex 12.1, 1 (vi) Important

Ex 12.1, 1 (vii)

Ex 12.1, 1 (viii) Important

Example 2 Important

Example 1

Ex 12.1, 2 (i)

Ex 12.1, 2 (ii) Important

Ex 12.1, 2 (iii) You are here

Ex 12.1, 2 (iv) Important

Ex 12.1, 2 (v)

Ex 12.1, 2 (vi)

Ex 12.1, 2 (vii)

Ex 12.1, 2 (viii) Important

Ex 12.1, 2 (ix)

Ex 12.1, 2 (x) Important

Last updated at April 16, 2024 by Teachoo

Ex 12.1, 2 (Method 1) Factorise the following expressions. (iii) 7𝑎^2 + 14a7𝑎^2 + 14a = 7𝑎^2 + (7 × 2) a = (7a × a) + (7a × 2) Taking 7a common, = 7a (a + 2) Ex 12.1, 2 (Method 2) Factorise the following expressions. (iii) 7𝑎^2 + 14a7𝑎^2 + 14a 7𝒂^𝟐 = 7 × 𝑎^2 = 7 × a × a 14a = 14 × a = 7 × 2 × a So, 7 and a are the common factors. 7𝑎^2 + 14a = (7 × a × a) + (2 × 7 × a) = (7 × a) (a + 2) = 7a (a + 2)